KONSEP KOMUNIKASI ISLAM DALAM SUDUT PANDANG FORMULA KOMUNIKASI EFEKTIF - Islami, Dian Ismi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2013)
This study entitled Concept of Islam in Perspective Communication Effective Communication, the problem is how Islam views the activities of communication, how communication in the Qur'an, Hadith and interpretation of the scholars of Islam and how the concept of communication in effective communication standpoint formulaThis research focused on the study of the verses of the Qur'an and its interpretation, hadith and books on propaganda and media and mass communication. This study uses qualitative textual analysis; including grammar and style analysis Arabic Arabic commonly known as Balagha and methods of semiotic analysis; paradigm and syntagmatic analysis of the text and narration.Communication patterns based on the theory Lasswell Islam there are five patterns, the first pattern of God as a communicator with the communicants are prophets, apostles, and the entire human race with a conduit or intermediary angel Gabriel massage or messages conveyed in the form of Islamic law in the form of goals or targets with human safety.